(3GdChL aj NHQ YhLs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3eG Jbhd GdSGOI GdYdeGA ai YhL Hf Yfb s
(3BNQgG (B:s
(3gPG GdbOQ GdPi jMJed Hbhdg GfJgi hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U H (B123 - (3U H (B215s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B151 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B87 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B56 s
(3eUOQ GbJfGA GdCUd (B:s
(3QhGb GdCJQGc (B- (3GdCRgQ (B(3698) s
Keywords: (3GdJGQjNs